The Annotated Luther, Volume 4 : Pastoral Writings - Luther, Martin, 1483-1546 (Annotated Luther ;, 2016)
Volume 4 of The Annotated Luther series presents an array of Luther's writings related to pastoral work. Luther's famous Invocavit Sermons and other selected sermons show a forthright and lively preacher. Hymn texts reveal Luther's grasp of hymnody as a tool for conveying and expressing faith. His Small Catechism as well as several pieces on prayer, including his Personal Prayer Book and A Simple Way to Pray, show his engagement in the basic task of teaching the faith. Luther's prefaces to his own writings contain personal reflections on his reforming work. Also in this volume are his commentary on The Magnificat, selected letters, and shorter pieces that display his pastoral responses to particular situations: Sermon on Preparing to Die, Whether One May Flee from a Deadly Plague, and Comfort for Women Who Have Had a Miscarriage. Each volume in The Annotated Luther series contains new introductions, annotations, illustrations, and notes to help shed light on Luther's context and interpret his writings for today. The translations of Luther's writings include updates of Luther